Simulation-based performance evaluation of reconfigurable intelligent surface (RIS)-assisted non-orthogonal multiple access (NOMA) networks - Ikoko Precious; Samuel Oghenemega Shaka; Enoh Pius Ogherohwo; Cletus Olisenekwu; Oyibo Dafe Precious (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2025)
The integration of reconfigurable intelligent surfaces (RIS) into non-orthogonal multiple access (NOMA) networks presents a promising solution to the persistent interference and inefficiency challenges of modern wireless communication systems. This study investigates the impact of RIS on the performance of downlink NOMA networks using a simulation-based approach in MATLAB Simulink. The objective is to evaluate how RIS can enhance signal quality, reduce bit error rate (BER), improve spectral and energy efficiency, and minimize latency in densely connected environments. The methodology involves modeling a system with a base station, multiple users, and a RIS layer, analyzing various RIS configurations such as the number of reflecting elements and user distances ranging from 200 m to 1000 m. Results show that RIS-assisted NOMA significantly boosts signal-to-interference-plus-noise ratio (SINR) across all user pairs, achieving an average SINR gain of 6 dB e.g., SINR for users at 200 m improved from 12.5 dB to 18.7 dB. Similarly, BER dropped by up to 80%, spectral efficiency increased by 1 bps/Hz, and energy efficiency rose by 35%. Furthermore, outage probability reduced by more than 50%, and latency improved by approximately 3ms on average. These findings demonstrate the capacity of RIS to create a smart radio environment that overcomes path loss and interference bottlenecks, offering a scalable, energy-efficient, and low-latency solution for next-generation wireless networks.